Heterogeneity of cancer-associated fibroblasts and tumor-promoting roles in head and neck squamous cell carcinoma - El Herch, Imane; Tornaas, Stian; Dongre, Harsh Nitin; Costea, Daniela Elena (Frontiers in Molecular Biosciences, 2024)
Tumor microenvironment (TME) in head and neck squamous cell carcinoma (HNSCC) has a major influence on disease progression and therapy response. One of the predominant stromal cell types in the TME of HNSCC is cancer-associated fibroblasts (CAF). CAF constitute a diverse cell population and we are only at the beginning of characterizing and understanding the functions of various CAF subsets. CAF have been shown to interact with tumor cells and other components of the TME to shape mainly a favourable microenvironment for HNSCC progression, although some studies report existence of tumorrestraining CAF subtypes. The numerous pathways used by CAF to promote tumorigenesis may represent potential therapeutic targets. This review summarizes current knowledge on the origins, subtypes and mechanisms employed by CAF in HNSCC. The aim is to contribute to the understanding on how CAF actively influence the TME and modulate different immune cell types, as well as cancer cells, to establish a conducive setting for cancer growth. Although CAF are currently a promising therapeutic target for the treatment of other types of cancer, there is no significant therapeutic advancement in HNSCC.